(untitled) (Eurasian Journal of Ecology, 2016)
Reservation of natural populations by methods of artificial breeding needs in using all genetic diversity of breeders. However now aquaculturists have to reject the female sturgeons having oocytes with low degree of polarization and average weight below definitive value at the beginning of spring spawning season. The shortage of mature males is one of the factors limiting possibilities of spring breeding period prolongation for maturation of females with retarded vitellogenesis. The possibilities of Russian sturgeon male spermiation prolongation by the supplemental injections of sturgeon glycerol pituitary preparation (GPP) or synthetic superactive LH-RH analogue (surfagon) were investigated. The data showed that the optimal doses of both preparations and their comparative effectiveness depend on water temperature and intervals between injections. The histological changes of testis structure after multiple injections were demonstrated. The continued decline of spermatozoa content in seminal tubules took place during this process making impossible 4-th injection. The testosterone and 11-ketotestosterone blood serum levels had been measured by enzyme linked immuno-sorbent assay (ELISA). The slight increase of both androgens at the moment of induction of spermiation (12 hours after 1-st injection) was followed by their sharp decline. The supplemental injections of GPP or surfagon stimulated enforcement or even re-starting of spermiation but did not induce new androgen level’s elevations. Significant differences in influence of two preparations on androgen’s profiles were not observed. The data indicates the possibilities of supplemental hormonal treatment of Russian sturgeon males and likely the males of others sturgeon species for spermiation prolongation and their reproductive potential maximal using.